Program Evaluation of Implementation Science Outcomes From an Intervention to Improve Compliance With Chlorhexidine Gluconate Bathing: A Qualitative Study. - Reynolds, Staci S.; Woltz, Patricia; Keating, Edward; Neff, Janice; Elliott, Jennifer; Granger, Bradi B. (Dimensions of Critical Care Nursing)
Background and Objectives: Evaluation of implementation science research is warranted to better understand and determine the success of translating evidence-based infection prevention practices at the bedside. The purpose of this program evaluation was to evaluate implementation outcomes from the perspectives of nurses and nursing leaders regarding a previously conducted chlorhexidine gluconate (CHG) bathing implementation science study among 14 critical care units. Methods: Focus groups and interviews, using semistructured interview questions, were conducted to examine the perceptions of nurses who participated in a CHG bathing implementation science study. A deductive qualitative analysis using Proctor and colleagues' implementation outcomes framework was used. Transcripts were analyzed and categorized using the framework as a predetermined code list to structure the implementation outcomes of acceptability, appropriateness, adoption, feasibility, and sustainability. Findings: A total of 19 nurses and nurse leaders participated in a focus group or interview. Participants noted that both implementation strategies used in the initial study (educational outreach and audit and feedback) were acceptable and appropriate and expressed that the evidence-based CHG bathing practice was feasible to integrate into practice and was being adopted. Discussion: The program evaluation identified strengths and opportunities for improvement related to the implementation strategies and evidence-based CHG bathing protocol. Findings can inform future studies that seek to implement CHG bathing protocols in the critical care setting using audit and feedback and educational outreach strategies.